Pengaruh Umur Ibu yang Beresiko Kanker Serviks dan Tingkat Pendidikan Ibu dengan Kanker Serviks di Ruang Poli Kandungan RSUD Ulin Banjarmasin - Diaty, Rima; Arisa, Azura; Ari Lestari, Nur Cahyani; Utami, Syahrida Wahyu; Purwanti, Sri (JURNAL KEBIDANAN BESTARI, 2022)
Background: Cervical cancer in Indonesia is the number 1 cancer with an estimate that every 1 hour a woman dies of cervical cancer. In Indonesia, the number of cervical cancers is made worse by the fact that many (70%) cases are already at an advanced stage when they come to the hospital. Based on the register data in the obstetrics ward of Ulin Hospital Banjarmasin, 68 people were affected by cervical cancer. Objective: This study aims to determine the age of the mother at risk of cervical cancer and the education level of the mother with cervical cancer at the Ulin Hospital Banjarmasin. Methods: This study used a descriptive method, the population was all mothers who were examined for cervical cancer in the obstetrics poly room at Ulin Hospital Banjarmasin totaling 68 people. Sampling with saturated sampling method, namely by taking all the population as a sample. Data collection is taken from the data register book. Data processing is summed, tabulated and presented, for further descriptive analysis to determine the age of the mother at risk of cervical cancer and the level of education that can affect the occurrence of cervical cancer. Results: The results of the research in the gynecology poly room of Ulin Hospital Banjarmasin, namely the number of mothers with cervical cancer aged over 35 years were 67 people (98.53%) and mothers with cervical cancer with a low level of education (SD) were 36 people (52, 94%). Conclusion: Based on research that has been conducted on 68 mothers who experienced cervical cancer at Ulin Hospital Banjarmasin, it can be concluded that the age of mothers who are at risk for cervical cancer is mostly (> 35 years) as many as 67 people (95.6%). The education level of mothers who experienced cervical cancer was mostly (SD) as many as 36 people (52.94%). Keywords: Cervical cancer, age at risk for cervical cancer, education level.